Full-order and reduced-order observers for linear parameter-varying systems with one-sided Lipschitz nonlinearities and disturbances using parameter-dependent Lyapunov function. Issue 10 (July 2019) - Abdullah, Ali; Qasem, Omar
Highlights: This work considers the design of observer for linear parameter-varying (LPV) systems. The LPV systems under consideration with one-sided Lipschitz nonlinearities and disturbances. Full-order and reduced-order observers are designed in this study. The observers are designed using parameter-dependent Lyapunov functions. Robust stability conditions are formulated as solvable LMI conditions. These observers are applied in simulation and real-time into two practical examples. Abstract: In this study, H ∞ full-order and reduced-order observers are designed for a class of linear parameter-varying (LPV) systems with one-sided Lipschitz nonlinearities and disturbances. Parameter-dependent Lyapunov function is used to analyze the robust stability of the proposed observers. Three practical examples are used to demonstrate the usefulness of the proposed observers. Simulation and experimental results indicate that the proposed observers work well.